Android how to program - Deitel, Paul J.; Deitel, Harvey M. 1945-; Deitel, Abbey (Pearson Education Limited, 2015)
Android How to Program, Second Edition provides a clear and entertaining App-driven introduction to Android 4.3 development for both introductory- and intermediate-level programming courses. The Deitels' App-driven, Live Code Approach is simply the best way to master Android programming! The Deitels teach Android programming through ten complete, working Android Apps. Each chapter presents new concepts through a single App. The authors first discuss what the App does, show screen shots, test drive the App, and present an overview of the technologies and architecture used to build it